Pelatihan Digital Marketing Dalam Meningkatkan Strategi Pemasaran UMKM Desa Bancer - Melyani, Vidia Ananda; Farahdiansari, Ardana Putri; Rohmah, Alfiatur; Fadilah, M. Farid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Digital Marketing Training in improving MSME marketing strategies is an activity directed to help MSMEs reach a wide market through the use of digital technology. Digital technology is used by various groups of people, including MSME actors. However, due to the lack of knowledge and awareness of MSME actors in Bancer Village, Ngraho District, Bojonegoro Regency, digital technology has not been utilized optimally in supporting business processes. As an effort to solve these problems, digital marketing training was held. Through this digital marketing training, it will help increase sales of Bancer Village MSMEs. Collaborative Thematic KKN students of group 19 of Bojonegoro University collaborated with the East Java Super Corridor (EJSC) Bakorwil Bojonegoro and Creative (Information and communication technology) in digital marketing training, this activity covered a variety of important materials, ranging from the basics of digital marketing, social media management, to the creation of interesting content. The training was attended by 19 participants from MSME actors, including MSMEs furniture, crackers, ledre and helmets. Collaborative Thematic KKN students of group 19 participate in providing periodic assistance in an effort to improve product marketing performance through social media. to the creation of interesting content. The training was attended by 19 participants from MSME actors, including MSMEs furniture, crackers, ledre and helmets. Collaborative Thematic KKN students of group 19 participate in providing periodic assistance in an effort to improve product marketing performance through social media.